Biodegradable polymers in clinical use and clinical development - Domb, A. J. (Abraham J.); Jain, Jay Prakash (Hoboken, N.J. : Wiley, 2011)
"This book focuses on biodegradable polymers that are already in clinical use or under clinical development. Synthetic and natural polymers will be included. This excludes polymers that have been investigated and did not reach clinical development. The purpose of this book is to provide updated status of the polymers that are clinical use and those that are now being developed for clinical use and hopefully will reach the clinic during the next 5 years. The book provides information that of interest to academics and practicing researchers including chemists, biologists and bioengineers and users: physicians, pharmacists"--
Biodegradable Polymers in Drug Delivery / Jay Prakash Jain, Wubeante Yenet Ayen, Abraham J Domb, Neeraj Kumar -- Biodegradable Polymers of Natural Origin: Protein-Based Polymers. Collagen / Wahid Khan, Deepak Yadav, Abraham J Domb, Neeraj Kumar -- Properties and Hemostatic Application of Gelatin / Jalindar Totre, Diana Ickowicz, Abraham J Domb -- Biodegradable Polymers of Natural Origin: Polysaccharides. Chitosan and Its Derivatives in Clinical Use and Applications / Anuradha Subramanian, Kirthanashri Srinivasan Vasanthan, Uma Maheswari Krishnan, Swaminathan Sethuraman -- Clinical Uses of Alginate / Udi Nussinovitch, Amos Nussinovitch -- Dextran and Pentosan Sulfate -- Clinical Applications / Ramu Parthasarathi, A Jayakrishnan -- Arabinogalactan in Clinical Use / Rajendra P Pawar, Babasaheb A Kushekar, Bhaskar S Jadhav, Kiran R Kharat, Ravikumar M Borade, Abraham J Domb -- Biodegradable Polymers of Natural Origin: Polyesters. Polyhydroxyalkanoate / Kesaven Bhubalan, Wing-Hin Lee, Kumar Sudesh -- Synthetic Biodegradable Polymers. Lactide and Glycolide Polymers / Kevin Letchford, Anders S̲dergard, David Plackett, Samuel E Gilchrist, Helen M Burt -- Polyanhydrides-Poly(CPP-SA), Fatty-Acid-Based Polyanhydrides / Ravikumar M Borade, Abraham J Domb, Archana A Sawale, Rajendra P Pawar, Kiran R Kharat -- Poly(?-Caprolactone--Glycolide): Biomedical Applications of a Unique Elastomer / Kevin Cooper, Aruna Nathan, Murty Vyakarnam -- Medicinal Applications of Cyanoacrylate / Rajendra P Pawar, Ashok E Jadhav, Sumangala B Tathe, Bhimrao C Khade, Abraham J Domb -- Polyethylene Glycol in Clinical Application and PEGylated Drugs / Teerapol Srichana, Tan Suwandecha -- Inorganic Polymers. Calcium-Phosphate-Based Ceramics for Biomedical Applications / Qing Lv, Kevin W-H Lo, Lakshmi S Nair, Cato T Laurencin -- Biodegradable Polymers for Emerging Clinical Uses. Biocompatible Polymers for Nucleic Acid Delivery / Jeff Sparks, Khursheed Anwer -- Biodegradable Polymers for Emerging Clinical Use in Tissue Engineering / Shalini Verma, Kalpna Garkhal, Anupama Mittal, Neeraj Kumar -- Injectable Polymers / Shimon A Unterman, Norman A Marcus, Jennifer H Elisseeff -- IPR Aspects of Biodegradable Polymers. Global Patent and Technological Status of Biodegradable Polymers in Drug Delivery and Tissue Engineering / Parikshit Bansal, Shalini Verma, Wahid Khan, Neeraj Kumar -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Polymers in medicine; Biodegradable plastics; Biodegradable Plastics; Polymers; Medicine; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; MEDICAL -- Instruments & Supplies; Biodegradable plastics; Polymers in medicine; Electronic books; Electronic resource